2016
DOI: 10.15395/mkb.v48n2.763
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Hemodialisis Terhadap Kejadian Kurang Pendengaran Sensorineural Pada Penderita Gagal Ginjal Kronik

Abstract: AbstrakKurang pendengaran sensorineural (KPSN) dapat terjadi pada kasus gagal ginjal kronik (GGK) yang dilakukan hemodialisis (HD). KPSN akibat HD terjadi pada berbagai frekuensi. Faktor yang diduga dapat memengaruhi adalah usia, hipertensi, dan diabetes melitus (DM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 11 publications
(12 reference statements)
2
7
1
Order By: Relevance
“…Hearing loss is more obvious in the elderly and patients who had received fewer hemodialysis sessions. Ulfa et al 6 found in their study, out of 26 subject on hemodialysis, 8 had SNHL consisted of 7 in low grade and 1 moderate grade.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Hearing loss is more obvious in the elderly and patients who had received fewer hemodialysis sessions. Ulfa et al 6 found in their study, out of 26 subject on hemodialysis, 8 had SNHL consisted of 7 in low grade and 1 moderate grade.…”
Section: Discussionmentioning
confidence: 83%
“…Chronic ongoing DM lead to severe glomeruli impairment which marked by the decrease of GFR and increased creatinine level. 10 Ulfa et al 6 found in their study that there was no correlation between hypertension and DM with the incidence of SNHL, but hemodialysis affect the occurrence of SNHL. Bainbridge at al.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Some literature reports that hemodialysis has no effect on hearing function in at least the first five years of treatment, while some report hemodialysis affects hearing acuity (4) . Chronic Kidney Disease patients who undergo 3 sessions of hemodialysis have an effect on the sensorineural type hearing loss significantly (5) . A positive correlation was found between hearing loss and the frequency of hemodialysis (6) .…”
Section: Introductionmentioning
confidence: 99%